Nephrectomy for Metastatic Kidney Tumor in Patients with Differentiated Thyroid Cancer: A Report of Two Cases - Haruhiko Yamazaki; Takeshi Kishida; Go Noguchi; Hiroyuki Iwasaki; Nobuyasu Suganuma; Katsuhiko Masudo; Hirotaka Nakayama; Toshinari Yamashita; Takashi Yamanaka; Yuko Sugawara; Yuka Matsubara; Kaori Kohagura; et al. (Case Reports in Endocrinology)
The occurrence of renal tumors originating from thyroid cancer is extremely rare with a few effective treatments for renal metastases. Here, we report the cases of two patients with differentiated thyroid cancer who underwent nephrectomy for a metastatic kidney tumor. Case 1 was a 74-year-old man who was diagnosed with right kidney tumor 10 years after initial surgery for papillary thyroid cancer (PTC). Right nephrectomy was performed, and the pathology was metastatic PTC. Case 2 was a 68-year-old woman who was diagnosed with left kidney tumor 24 years after surgery for follicular thyroid carcinoma (FTC). Left nephrectomy was performed, and the pathology was metastatic FTC. Nephrectomy for single renal metastasis could be considered a treatment option if the patients’ general condition is positive.